2021
DOI: 10.1038/s41388-021-01956-6
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived lysophosphatidic acid mediated LPAR1 activation as a therapeutic target for osteosarcoma metastasis

Abstract: Osteosarcoma is the most common primary malignant bone cancer, with high rates of pulmonary metastasis. Osteosarcoma patients with pulmonary metastasis have worse prognosis than those with localized disease, leading to dramatically reduced survival rates. Therefore, understanding the biological characteristics of metastatic osteosarcoma and the molecular mechanisms of invasion and metastasis of osteosarcoma cells will lead to the development of innovative therapeutic intervention for advanced osteosarcoma. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 53 publications
(63 reference statements)
0
19
0
Order By: Relevance
“…For example, osteosarcoma cells usually show high platelet activation inducing characteristics, which can induce platelet activation. Activated platelets secrete LPA and CLEC, which enhance the invasive ability of osteosarcoma through the LPA-LPAR1 axis and the interaction between platelet CLEC-2 and osteosarcoma podoplanin (37,38). And tumor cells can release soluble mediators such as ADP (16) to activate platelets and form polymers through TCIPA on the surface of tumor cells, so that platelets can wrap tumor cells, thus avoiding the attack of immune cells in the circulatory system (39).…”
Section: Discussionmentioning
confidence: 99%
“…For example, osteosarcoma cells usually show high platelet activation inducing characteristics, which can induce platelet activation. Activated platelets secrete LPA and CLEC, which enhance the invasive ability of osteosarcoma through the LPA-LPAR1 axis and the interaction between platelet CLEC-2 and osteosarcoma podoplanin (37,38). And tumor cells can release soluble mediators such as ADP (16) to activate platelets and form polymers through TCIPA on the surface of tumor cells, so that platelets can wrap tumor cells, thus avoiding the attack of immune cells in the circulatory system (39).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated research has revealed the decreased expression of LPAR1 and its migration-inhibiting effects in tumors including prostate cancer, gastric cancer and pancreatic cancer, which is consistent with our results [ 7 , 12 , 13 ]. However, LPAR1 expression has also been reported to be significantly increased in other tumors, such as human hepatic cancer [ 29 ], osteosarcoma [ 30 ] and ovarian cancer [ 31 ], and to exert tumor-promoting effects directly or mediated by chemotherapy resistance [ 30 , 32 ]. The controversial research results about LPAR1 suggest its different signaling transduction pathways and functions in different types of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that when osteosarcoma cells come into contact with platelets in the bloodstream, platelets are activated, and the invasive potential is enhanced via LPA produced and released from the activated platelets, resulting in lung metastasis. This indicates that LPAR1 antagonist administration may inhibit pulmonary metastasis of osteosarcoma [ 44 ]. CAVIN1/PTRF, which is specifically expressed in HMOS as revealed in this study, should also be investigated with antagonists.…”
Section: Discussionmentioning
confidence: 99%